Multimodal Imaging of Autofluorescent Sites Reveals Varied Chemical Speciation in SSZ‐13 Crystals. (25th January 2021) - Omori, Naomi; Candeo, Alessia; Mosca, Sara; Lezcano‐Gonzalez, Ines; Robinson, Ian K.; Li, Luxi; Greenaway, Alex G.; Collier, Paul; Beale, Andrew M.
Abstract: A multimodal imaging study of chabazite is used to show the distribution of and discriminate between different emissive deposits arising as a result of the detemplation process. Confocal imaging, 3D fluorescence lifetime imaging, 3D multispectral fluorescence imaging, and Raman mapping are used to show three different types of emissive behaviours each characterised by different spatial distributions, trends in lifetime, spectral signals, and Raman signatures. A notable difference is seen in the morphology of agglomerated surface deposits and larger subsurface deposits, which experience lifetime augmentation due to spatial confinement. The distribution of organic residue throughout the crystal volume is comparable to XRF mapping that shows Si enrichment on the outer edges and higher Al content through the centre, demonstrating that a fluorescence‐based technique can also be used to indirectly comment on the compositional chemistry of the inorganic framework. Abstract : A multimodal imaging study of chabazite is used to analyse emissive deposits. A notable difference is seen in the morphology of agglomerated surface deposits and larger subsurface deposits. Comparison of the distribution of organic residue throughout the crystal volume and XRF mapping is demonstrating that a fluorescence‐based technique can also be used to indirectly comment on the compositional chemistry of the inorganic framework.